HUBUNGAN KARAKTERISTIK IBU HAMIL DENGAN KEJADIAN ABORTUS DI RUANG RAWAT INAP KEBIDAN RSD RADEN MATTAHER JAMBI TAHUN 2009 - Yusnaini Yusnaini (Jurnal Ilmiah Universitas Batanghari Jambi, 2010)
Incidence of abortion is one indicator of the cause of the increased maternal mortality (MMR). In Jambi an increase in the incidence of abortion from the years 2008-2009. This study aims to obtain a picture of maternal characteristics that may affect the incidence of abortion in Room Inpatient Obstetric RSD Raden Mattaher Jambi including maternal age, gravida status of mothers and mother's education level.The research design used in this research is to study the documentation using the method of case-cotrol by comparing the number of cases with the control, taken in a retrospective study design samples. Total keseluruahn sample in this study amounted to 220 people with a ratio of 1:1 which totaled 110 cases and 110 people total control of the entire population of women who experienced abortion and abortion was not in Room Inpatient Obstetric RSD Raden Mattaher Jambi from October to April in 2009.Data collection was taken by looking at their medical data and registers pasien.yang experienced abortion and no abortion. From the test results (Chi-square) results showed a significant correlation between the incidence of abortion with maternal age, gravida status of mothers and maternal educational level with p-value for each variable: maternal age (0.000), gravida status of mothers (0.015) and maternal education level (0.000). Based on the results of this study can be recommended for health care institutions to further improve the quality of pre-natal care and provide health education or counseling in a more intensive and interesting in order to provide knowledge, particularly for mothers about the causes of abortion on maternal characteristics and complications that can be caused by abortion, but it also needs more developed community role particularly in mengkapanyekan family health programs, especially maternal and child health to the public.Keyword : Abortus,Gravida,  Education Level